Do Experiences Studying Abroad Promote Dialectical Thinking? Empirical Evidence From Chinese International Students - Hu, Xiaomeng; Wang, Yang; Liao, Shanhui; Peng, Kaiping (Frontiers in Psychology, 2021)
Our current work seeks to provide direct empirical evidence on whether Chinese international students’ experiences studying abroad promote dialectical thinking. We collected behavioral data from 258 Chinese international students studying in multiple regions. We found that there was a main effect among the four conditions (i.e. studying abroad, exposure to foreign culture, hometown, and typical day). More specifically, when primed with studying abroad or typical day (relative to hometown culture), participants were more likely to show tolerance for contradiction by deeming both sides of contradictory scientific statements as convincing and rating them more favorably. Therefore, it is plausible that Chinese international students’ experiences studying abroad promote their dialectical thinking. More work is needed to further this line of research by 1) extending these effects with other measures of dialectical thinking such as perception of interconnectedness and prediction of change, 2) adopting differing paradigms to provide more robust findings, and 3) probing the underlying processes as to why experiences studying abroad promote dialectical thinking.